Comparative Analysis of the Financial Results-Equity in Family Firms and Non-Family Firms: The Case of the Service Sector in Malaga (Spain) - García-Palomo, Noemí; Vila-Oblitas, José R. (European Journal of Family Business, 2018)
This research explores the differences between the main economic financial ratios of family firms and non-family firms. The analysis has been carried out on a total of 335 firms from within the province of Malaga, of which 154 are family firms, with the remaining 181 being non-family firms. The sector that is the subject of this study is the tertiary sector: choosing bars, cafes and wholesale providers of these type of businesses due to their evident importance to the service sector in the province. Among main results, significant differences are highlighted in all the ratios analysed between the two groups of firms studied, as well as a greater distribution of profits to its shareholders by family firms (FF) versus non-family firms (NFF). Results show NFF have relatively higher economic return, although the variation of this ratio is greater than in a family firm.